Determination of Tetracycline Antibiotic Residue Levels in Goldfish (Cyprinus carpio) using High Performance Liquid Chromatography (HPLC) - Agung Abadi Kiswandono; Anisa Rahmawati; Yanesta Oxvyena; Purna Pirdaus; Sonny Widiarto; Sutopo Hadi; Rinawati Rinawati (UNIVERSITAS SEBELAS MARET (UNS), 2026)
The method for determining residual levels of tetracycline antibiotics in goldfish (Cyprinus carpio) was validated using High Performance Liquid Chromatography (HPLC). The HPLC method has advantages, including high accuracy, efficiency, ease of operation, and high selectivity and sensitivity. This research aims to develop a method for determining tetracycline residues and tetracycline levels in goldfish meat obtained from eight markets in Bandar Lampung City. The analytical method carried out was optimized for the composition and flow rate of the mobile phase. Optimization results show a composition of acetonitrile:water = 35:65 and a flow rate of 0.5 mL/minute. The method validation parameters carried out are linearity, precision, accuracy, selectivity, Limit of Detection (LoD), and Limit of Quantitation (LoQ). The linearity results obtained from this research were R2 = 0.9980. This method has repeatability precision with a Relative Standard Deviation (%RSD) value of 1.35%, and reproducibility precision with %RSD values of 0.96% and 1.14%, respectively. The %recovery method value is 101.05%. The LoD and LoQ values for this method are 0.27 and 0.90 ppm. Measurement of tetracycline antibiotic residue levels in carp samples from 8 market locations in Bandar Lampung showed values of 21.77 – 38.58 ppm, with uncertainties of ±0.87 – ±1.42. The method validation results show that the method can be used for routine analysis of tetracycline antibiotic levels in the laboratory.